Eosinophil progenitor levels correlate with tissue pathology in pediatric eosinophilic esophagitis - Schwartz, Justin T. (J Allergy Clin Immunol, 2018)
Blood eosinophil progenitors (EoPs) correlate with tissue pathology during active eosinophilic esophagitis (EoE), providing additional evidence for blood EoP levels as a biomarker for disease activity and suggesting a role for EoPs in EoE pathogenesis.